Enterprise Architecture Design Using the TOGAF ADM Framework at SMAS Setia Budi in Sungailiat - Andrian, Kelvin; Lee, Francka Sakti (Fakultas Teknik Universitas Muria Kudus, 2024)
SMAS Setia Budi is a private school in Sungailiat that wants to improve the quality of its educational services by using information technology systems. In carrying out its business processes, schools have not maximized the information system architecture in accordance with the needs of school business processes. Researchers found several problems that occurred in schools such as in terms of new student data collection, administrative and financial processes, problems with procurement of goods, and others. To help plan the development of information systems at SMAS Setia Budi, researchers designed a business architecture (enterprise architecture) using the TOGAF framework with the (ADM) method as a problem solving. In this study, an analysis of each phase in TOGAF was carried out, namely preliminary phase, vision architecture phase, business architecture phase, information systems architecture phase, technology architecture phase, and opportunities and solutions phase. The purpose this study is to recommend blueprints, namely five application blueprint consisting of Academic Systems, Non-Academic Systems, School Procurement Management, School Financial Management, and School Data Management. Design is expected to be a benchmark for the development of information systems at the SMAS Setia Budi school and assist the school in carrying business processes in schools to be effective.